PENGARUH RISIKO PERUSAHAAN, INTENSITAS ASET TETAP DAN UKURAN PERUSAHAAN TERHADAP AGGRESSIVE TAX AVOIDANCE - Muhammad Rizky; Windhy Puspitasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This study aims to examine the effect of corporate risk taking, intensity of fixed asset and firm size on aggressive tax avoidance. This study uses secondary data from is manufacturing company during 2016-2018. Techniques and sampling used are using by purposive sampling. The data analysis technique used is multiple regression with the help of Statistical Package For Social Science (SPSS). The results of this study indicate that first, corporate risk taking has a significant positive effect on aggressive tax avoidance where the significance value is 0,002 < 0.05. Second, intensity of fixed asset has a significant negative effect on aggressive tax avoidance where the significant value is 0.000 < 0.05. Third, firm size has a significant negative effect on agggressive tax avoidance where the significant value is 0.019 <0.05. The conclusion of the study shows: 1) The corporate risk taking has a significant positive effect on aggressive tax avoidance, 2) Intensity of fixed asset has a significant negative effect on aggressive tax avoidance, 3) Firm size has a significant negative effect on aggressive tax avoidance.